2023
DOI: 10.3390/f14050910
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Residual Stand Disturbances after Harvesting in Close-to-Nature Managed Forests

Abstract: Close-to-nature forestry is a viable option to manage forests that are resilient to the challenges presented by climate change. The new silvicultural schemes necessitate adapting the operational side, posing challenges to productivity and the environmental effects of harvesting machinery and technologies. This study focused on analysing the disturbance of residual stands and forest soils in stands that were being restructured into multistorey, close-to-nature managed ones using low-impact forest harvesting tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Our results provided that the damage frequency was lower for the mechanized row-thinning, compared to the manual thinning. Similar results were obtained by Magagnotti et al [23]. Akay et al [24], Cudzik et al [5], Kizha et al [7], and Suhartana et al [25] reported that the most damage occurs during tree felling and extraction by machine traffic and log dragging and loading from the stump to the landing.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results provided that the damage frequency was lower for the mechanized row-thinning, compared to the manual thinning. Similar results were obtained by Magagnotti et al [23]. Akay et al [24], Cudzik et al [5], Kizha et al [7], and Suhartana et al [25] reported that the most damage occurs during tree felling and extraction by machine traffic and log dragging and loading from the stump to the landing.…”
Section: Discussionsupporting
confidence: 81%
“…Trees less than 6 cm at DBH were rejected from the damage measurements. In addition, all injury sizes for the roots, bu s, and stems were assigned a severity index of 1-6 to assess the level of wound severity: 1 = negligible injury, damaged area below 10 cm 2 ; 2 = very light, damaged area of 50 cm 2 ; 3 = light, damaged area of 100 cm 2 ; 4 = medium, damaged area of 200 cm 2 ; 5 = heavy, damaged area of 300 cm 2 ; and 6 = very heavy, damaged area above 300 cm 2 [23]. In addition, all injury sizes for the roots, butts, and stems were assigned a severity index of 1-6 to assess the level of wound severity: 1 = negligible injury, damaged area below 10 cm 2 ; 2 = very light, damaged area of 50 cm 2 ; 3 = light, damaged area of 100 cm 2 ; 4 = medium, damaged area of 200 cm 2 ; 5 = heavy, damaged area of 300 cm 2 ; and 6 = very heavy, damaged area above 300 cm 2 [23].…”
Section: Field Data Collection and Analysismentioning
confidence: 99%